The effect of mergers and acquisitions : focus on employee job satisfaction of former employees of Smartcom in Vodacom SA - Rathogwa, Avhaathu Thelma (Stellenbosch : Stellenbosch University, 2008)
Thesis (MPhil (Information Science))--Stellenbosch University, 2008.